صورة الشعر الأندلسي في أبحاث بالنثيا وغومس - Bahjat, Munjid Mustafa (Hebron University, 2010)
At the outset, this research paper gives a general introduction of two well known orientalists, namely Angel Gonzalez Palencia, and Emilio Garcia Gomez. The paper discusses the characteristics of their methodologies in regards to two aspects that are Spanish spirit and issues related to heritage. Moreover, the paper introduces their vision regarding the relationship of Andalusian literature with its Eastern counter part, and the various Andalusian literary periods. Furthermore, the paper looks in detail at the critique of various poets among them Yahya Al-Ghazal, Ibn Abid Rabah, Abu Ishaq Al-Albiri, Al-Sharif Al-Taliq, Ibn Zaidoun, and Al-Mu’tamid bin Abad. The paper also sheds light on their methodology of comparative criticism between a number of poets namely, between Ibn Hani and Al-Zubaidi, between Ibn Zaidoun and Al-Humaidi, between Ibn Shahid and Ibn Hazm, between Al-Mutanbi and Ibn Hani, between Ibn Zamrak and Ibn Khafajah, and between Ibn Hazm and Abu Ishaq Al-Albiri. Finally the paper analyzes the general rules and the aesthetic standards of the two orientalists.